Characteristics, sources, and reactions of nitrous acid during winter at an urban site in the Central Plains Economic Region in China - Q. Hao; N. Jiang; R. Zhang; L. Yang; S. Li (Atmospheric Chemistry and Physics, 2020)
Nitrous acid (HONO) in the core city of the Central Plains Economic Region in China was measured using an ambient ion monitor from 9 to 31 January 2019. Measurement time intervals were classified into the following periods in accordance with the daily mean values of PM2.5: clean days (CDs), polluted days (PDs), and severely polluted days (SPDs). The HONO concentrations during CD, PD, and SPD periods were 1.2, 2.3, and 3.7 ppbv, respectively. The contributions of the homogeneous reaction, heterogeneous conversion, and direct emissions to HONO sources varied under different pollution levels. The mean values of the net HONO production of the homogeneous reaction (<msubsup>POH+NOnet</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="38pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="2b27b948c8101981cb7f1bdf33e07f81"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-20-7087-2020-ie00001.svg" width="38pt" height="17pt" src="acp-20-7087-2020-ie00001.png"/></svg:svg>) in CD, PD, and SPD periods were 0.13, 0.26, and 0.56 ppbv h−1, respectively. The average conversions of NO2 (CHONO) in CD, PD, and SPD periods were 0.72×10-2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="57pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="54a9590c7e2809822a0939f25ae5371d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-20-7087-2020-ie00002.svg" width="57pt" height="14pt" src="acp-20-7087-2020-ie00002.png"/></svg:svg>, 0.64×10-2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="57pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="d6b4bd5351c6f39ff41e689abf4b4f07"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-20-7087-2020-ie00003.svg" width="57pt" height="14pt" src="acp-20-7087-2020-ie00003.png"/></svg:svg>, and 1.54×10-2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="57pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="834af2a9209780df4dbc001f4ae29753"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-20-7087-2020-ie00004.svg" width="57pt" height="14pt" src="acp-20-7087-2020-ie00004.png"/></svg:svg> h−1, respectively, indicating that the heterogeneous conversion of NO2 was less important than the homogeneous reaction. Furthermore, the net production of the homogeneous reaction may have been the main factor in the increase of HONO under high-NOx conditions (i.e., when the concentration of NO was higher than that of NO2) at nighttime. Daytime HONO budget analysis showed that the mean values of the unknown source (Punknown) during CD, PD, and SPD periods were 0.26, 0.40, and 1.83 ppbv h−1, respectively. The values of <msubsup>POH+NOnet</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="38pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="62d4b79bc322fbae695bf61e94bf5344"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-20-7087-2020-ie00005.svg" width="38pt" height="17pt" src="acp-20-7087-2020-ie00005.png"/></svg:svg>, CHONO, and Punknown in the SPDs period were comparatively larger than those in other periods, indicating that HONO participated in many reactions. The proportions of nighttime HONO sources also changed during the entire sampling period. Direct emissions and a heterogeneous reaction controlled HONO production in the first half of the night and provided a contribution that is larger than that of the homogeneous reaction. The proportion of homogenization gradually increased in the second half of the night due to the steady increase in NO concentrations. The hourly level of HONO abatement pathways, except for OH + HONO, was at least 0.22 ppbv h−1 in the SPDs period. The cumulative frequency distribution of the HONOemission∕HONO ratio (less than 20 %) was approximately 77 %, which suggested that direct emission was not important. The heterogeneous HONO production increased when the relative humidity (RH) increased, but it decreased when RH increased further. The average HONO∕NOx ratio (4.9 %) was more than twice the assumed globally averaged value (2.0 %).